Progress in Poly (3‐Hexylthiophene) Organic Solar Cells and the Influence of Its Molecular Weight on Device Performance. Issue 28 (26th June 2018) - Wadsworth, Andrew; Hamid, Zeinab; Bidwell, Matthew; Ashraf, Raja S.; Khan, Jafar I.; Anjum, Dalaver H.; Cendra, Camila; Yan, Jun; Rezasoltani, Elham; Guilbert, Anne A. Y.; Azzouzi, Mohammed; Gasparini, Nicola; et al.
Abstract: Poly (3‐hexylthiophene) (P3HT) was an early frontrunner in the development of donor polymers to be used in organic photovoltaics. A relatively straightforward and inexpensive synthesis suggests that it may be the most viable donor polymer to use in large‐scale commercial organic solar cells. Replacing fullerenes with new electron acceptors has led to significant improvements in device performance and stability, with devices now able to exceed an efficiency of 7%. Past studies have reported a dependence of device performance on the molecular weight of the polymer in fullerene‐containing blends, however, with nonfullerene acceptors now showing promise a similar study was needed. P3HT blends, with two nonfullerene acceptors (O‐IDTBR and EH‐IDTBR), were probed using a number of polymer batches with varying molecular weights. O‐IDTBR was shown to exhibit a dependence on the polymer molecular weight, with optimal performance achieved with a 34 kDa polymer, while EH‐IDTBR displayed an independence in performance with varying polymer molecular weight. Probing the thermal and morphological behavior of the P3HT:O‐IDTBR blends suggests that an optimal morphology with pronounced donor and acceptor domains was only achieved with the 34 kDa polymer, and a greater degree of mixing was exhibited in the other blends, likely leading to poorer device performance. Abstract : Poly (3‐hexylthiophene) (P3HT) remains among the only scalable donor polymers to be used successfully in photovoltaics. In combination with fullerenes it has achieved a power conversion efficiency of 7.4%, which has since been exceeded by utilizing nonfullerene acceptors. In this work, the dependence of P3HT molecular weight on device performance has been investigated using two nonfullerene acceptors with differing crystallinities.